Pengaruh Latar Belakang Pendidikan, Ukuran Usaha dan Literasi Keuangan terhadap Perencanaan Keuangan UMKM Di Masa Pandemi Covid-19 - Cintia Sinaring Sinanding; Tantina Haryati (Universitas Batanghari Jambi, 2022)
Economic support in Indonesia during the Covid-19 pandemic is MSMEs. The aims of the study is to empirically test the influence of educational background, business size and financial literacy on the financial planning of MSMEs in South Surabaya during the Covid-19 pandemic. This research uses primary data with quantitative research types using WarpPLS 7.0, the sample in this study is MSMEs spread in the South Surabaya area. Data collection is carried out by questionnaires distributed directly by researchers to MSMEs in the South Surabaya Region using random sampling methods. Hypothesis testing is looking at the probability value (p-value). This study found that educational background and financial literacy had a significant effect on the financial planning of MSMEs in South Surabaya during the Covid-19 pandemic. This phenomenon shows that education background and financial literacy are important factors for MSMEs in South Surabaya during the Covid-19 pandemic in conducting financial planning